Pendampingan Sadar Wisata dan Pembuatan Jalur Interpretasi Wisata Trekking di Desa Sirnajaya melalui Program MBKM Membangun Desa Wisata - Maesa Quratuain; Revi Agustin Aisyianita; Amelia Dwi Juliana (Insan Kreasi Media, 2023)
This paper discusses the implementation of the MBKM (Community Development through Student Community Service) program in Sirnajaya Village, Bogor Regency, West Java, Indonesia. The program focuses on raising awareness among the local community about responsible tourism practices and creating a trekking interpretive trail. The concept of